Acculturation, sociodemographic and lifestyle factors associated with compliance with physical activity recommendations in the Mexican-American Mano A Mano cohort. Issue 11 (25th November 2015) - Chrisman, Matthew; Daniel, Carrie R; Chow, Wong-Ho; Wu, Xifeng; Zhao, Hua
Abstract : Objectives: Being physically active is important for health, and few Mexican-Americans meet national US physical activity recommendations. The aim of this study was to investigate sociodemographic, acculturation and lifestyle factors that were associated with meeting physical activity recommendations in this group. Design and setting: A cross-sectional analysis of a large population-based cohort study in southern Texas, USA. Participants: Between 2001 and 2011, 21 551 adult members of the Mexican-American Mano A Mano cohort completed baseline questionnaires on physical activity and other lifestyle factors. Outcomes: Meeting US physical activity recommendations was defined as participating in 150 min of moderate, or 75 min of vigorous, activity per week. Factors contributing to the likelihood of meeting physical activity recommendations were examined by sex and country of birth in multivariate logistic regression models. Results: Less than half of all men and less than a quarter of all women met US physical activity recommendations. Having some college education, greater acculturation and current alcohol use were each associated with greater odds of meeting physical activity recommendations in all groups except US-born men. Higher body mass index was associated with lower odds of meeting recommendations in US-born and Mexico-born women. Conclusions: Results demonstrate that factors associated with meeting physical activity recommendations differ by sex and country of birth. Tailored interventions to increase Mexican-Americans' activity levels to achieve health benefits should consider education, acculturation and alcohol use.